Evaluating Library Services Quality Using GDSS-AHP, LibQual and IPA - Muhammad Ihsan; Reza Pulungan; A Afiahayati (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2018)
Library services quality is one of the most vital parts in library management. Evaluation of the library services based on the perspective of users is important. In this paper, we propose a collaboration of GDSS-AHP (Group Decision Support System-Analytical Hierarchy Process), LibQual, and IPA (Importance-Performance Analysis) methods to evaluate library services quality. The collaboration of GDSS-AHP and LibQual is used to calculate the weight of each evaluation statement and the level of library services quality based on users’ perception and expectation. IPA is then used to determine the position of the value of each evaluation statement in IPA’s four quadrants to obtain the recommended level for the library services improvement. This study is conducted at the Library of the Ministry of Trade of Indonesia, involving four decision makers: a head librarian, a library academic expert, and two library practitioners. Fifty library visitors become respondents to assess the quality services questionnaires. Based on their responses, we obtain that users’ satisfaction level is at least satisfied by 76.49 %. Meanwhile, usability testing is also conducted on the developed system by using three observation elements: effectiveness, efficiency and satisfaction. The usability testing is performed on five respondents, one admin, and two decision makers, and results in an average usability level of 90.03%.